2020
DOI: 10.1186/s40246-020-00276-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of CRISPR/Cas9 to human-induced pluripotent stem cells: from gene editing to drug discovery

Abstract: Human-induced pluripotent stem cells (hiPSCs) and CRISPR/Cas9 gene editing system represent two instruments of basic and translational research, which both allow to acquire deep insight about the molecular bases of many diseases but also to develop pharmacological research. This review is focused to draw up the latest technique of gene editing applied on hiPSCs, exploiting some of the genetic manipulation directed to the discovery of innovative therapeutic strategies. There are many expediencies provided by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 92 publications
0
35
0
Order By: Relevance
“…Their tri-lineage differentiation potential together with their non-transformed status are obvious advantages of hPSCs over conventional immortalized human cell culture models. These inherent characteristics of hPSCs including the fact that stem cells are perfectly amenable to genetic modifications [ 34 , 35 ] make them a powerful tool for both, studies on the molecular basis of human diseases and hPDD [ 4 , 31 , 36 , 37 , 38 ]. On the other hand, as for most other cell types, traditional 2D cultivation of hPSCs and their differentiated derivatives exhibits inevitable technological limitations and conceptual biases.…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their tri-lineage differentiation potential together with their non-transformed status are obvious advantages of hPSCs over conventional immortalized human cell culture models. These inherent characteristics of hPSCs including the fact that stem cells are perfectly amenable to genetic modifications [ 34 , 35 ] make them a powerful tool for both, studies on the molecular basis of human diseases and hPDD [ 4 , 31 , 36 , 37 , 38 ]. On the other hand, as for most other cell types, traditional 2D cultivation of hPSCs and their differentiated derivatives exhibits inevitable technological limitations and conceptual biases.…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…In between, in a variety of studies, especially hiPSC-derived cells have been used for testing the efficacy and toxicity of different compounds [ 34 , 37 ]: hiPSC-derived cortical neurons were used to test the impact of 3838 compounds in Lesch-Nyhan disease [ 39 ] and 17,000 small molecules were tested for their anti-fibrotic effects in mesenchymal-like cells [ 40 ]. hiPSC-derived neurons, neural progenitor cells, and motor neurons have been generated to study the effects of the R33 molecule for Alzheimer’s disease, the effects of 135 compounds for Schizophrenia, and 1416 drugs for Amyotrophic lateral sclerosis, respectively [ 41 , 42 , 43 ].…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…In the current pandemic scenario, studies have found that CRISPR/Cas9 has potential applications to human-induced pluripotent stem cells (hiPSCs), ranging from gene therapy to the induction of the immunological response to specific virus infection, such as HIV and SARS-Cov-2 itself [ 113 ]. The potential applications of CRISPR/Cas9 and hiPSCs in antiviral response, including SARS-Cov-2 research, are centered around a testing platform meant to replicate the human lung, differentiating wild type (WT)-hiPSCs into pneumocytes type II [ 114 ], and treating them with pseudoviruses capable of replicating SARS-Cov-2 infection [ 115 ]. Although future prospects for therapeutic applications are still far from conclusive, especially as far as mutation-prone viruses such as SARS-Cov-2 are concerned, that may certainly be one way in which gene editing could be harnessed for the repression or the upregulation of genes that play a role in viral activity, in addition to the introduction of polymorphisms that could protect against or predispose to the viral infection [ 116 ].…”
Section: Beyond Therapeutic Safety and Efficacy Genome Editing Entails Polarizing Ethical And Legal Quandariesmentioning
confidence: 99%
“…The implementation of iPSCs in personalized medicine has dramatically benefited from the recent advancements in DNA editing techniques, i.e., the 2020 Nobel-awarded development of the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated system 9 (Cas9) genome engineering tool [ 79 ]. CRISPR/Cas9-editing applied to the iPSC genome is widely exploited in translational precision medicine research for the development of novel cell-based therapeutic strategies and in the early phases of drug discovery [ 80 , 81 , 82 , 83 , 84 ]. Precisely, the artificial CRISPR system for gene editing consists of two essential components, a guide RNA (gRNA) to target complementary DNA sequences for cleavage and the CRISPR-associated protein (Cas), an RNA-guided DNA endonuclease found in Streptococcus pyogenes, which generates site-specific double-strand breaks based on the gRNA-defined sequence [ 85 , 86 ].…”
Section: Stem Cells In Personalized Medicinementioning
confidence: 99%